Effect Of Family Support Toward Patient Compliance In Taking Pulmonary Tuberculosis Medication At BPKM The City Of Pekalongan - Ahmad Baequny; Suryo Pratikwo; Arif Hilal Iman (Jurnal Riset Kesehatan, 2013)
The aim of this research was to know effect of the family support toward patient compliance within taking tuberculosis medication at BPKM the city of Pekalongan. This research was descriptive correlation with cross sectional design. Questionnaire was used as an instrument that was distributed to 60 respondents. Data was analyzed by Chi square test. The result of the research showed that there was an effect of the family support among aspects of support social , moral, material, and support of motivation for TB drug compliance at BPKM Pekalongan city (p value:0,000 – 0,003). To increase of patient compliance, it is recomendated for family to give endorsement within TBC medication, family also gives concern and prevent TBC transmission in order to decrease the cases.